2012
DOI: 10.1103/physrevlett.109.155001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Dynamic Interactions between Fundamental and Second-Harmonic Modes in a High-Power Sub-Terahertz Gyrotron Operating in Regimes of Soft and Hard Self-Excitation

Abstract: Dynamic mode interaction between fundamental and second-harmonic modes has been observed in high-power sub-terahertz gyrotrons [T. Notake et al., Phys. Rev. Lett. 103, 225002 (2009); T. Saito et al. Phys. Plasmas 19, 063106 (2012)]. Interaction takes place between a parasitic fundamental or first-harmonic (FH) mode and an operating second-harmonic (SH) mode, as well as among SH modes. In particular, nonlinear excitation of the parasitic FH mode in the hard self-excitation regime with assistance of a SH mode in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…At present, it is commonly accepted that by using the available methods of machining, one can manufacture relatively long (tens of wavelengths λ) cylindrical cavities with diameters 2R greater than 2.5-3 mm with a small error (less than 0.01λ). Analyzing the mode spectrum and considering the experimental data [25,26], the TE 8,5 mode at the second harmonic has been selected as the operating one. This mode had been used successfully at frequencies of about 250 GHz [25], but at high-power regimes with increase of the beam current, its suppression by the fundamental harmonic had been observed [26].…”
Section: Selection Of the Operating Modementioning
confidence: 99%
See 1 more Smart Citation
“…At present, it is commonly accepted that by using the available methods of machining, one can manufacture relatively long (tens of wavelengths λ) cylindrical cavities with diameters 2R greater than 2.5-3 mm with a small error (less than 0.01λ). Analyzing the mode spectrum and considering the experimental data [25,26], the TE 8,5 mode at the second harmonic has been selected as the operating one. This mode had been used successfully at frequencies of about 250 GHz [25], but at high-power regimes with increase of the beam current, its suppression by the fundamental harmonic had been observed [26].…”
Section: Selection Of the Operating Modementioning
confidence: 99%
“…Analyzing the mode spectrum and considering the experimental data [25,26], the TE 8,5 mode at the second harmonic has been selected as the operating one. This mode had been used successfully at frequencies of about 250 GHz [25], but at high-power regimes with increase of the beam current, its suppression by the fundamental harmonic had been observed [26]. The double-beam scheme gives a chance to widen the operational parameter space and particularly to increase significantly the beam current and thus the output power of the generated radiation.…”
Section: Selection Of the Operating Modementioning
confidence: 99%
“…The electron cyclotron maser (ECM), which is based on the stimulated cyclotron emission process involving energetic electrons in gyrational motion, has undergone a remarkably successful evolution from theoretical research to device implementation. Nowadays, ECM‐based devices are important, coherent, high‐power microwave sources, which have numerous applications in plasma diagnostics, particle accelerators, advanced radars, and industrial processing . The resonance condition of the ECM is ω = k z v z + s Ω, in which ω , k z , v z , s and Ω = eB / m 0 γc are the microwave angular frequency, axial wave number, axial velocity of electron, harmonic numbers, and relativistic electron cyclotron frequency, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although the conventional techniques, including large-orbit operation [22]- [24] and special interaction circuit [25], [26], are previously developed to suppress the mode competition, there is still lack of an effective solution to realize high efficiency in a high-harmonic gyrotron (s ≥ 3) and simultaneously suppress the mode competition. A start-up scenario of active parameter control is widely used in the hard-excited gyrotrons [27]- [30] operating on fundamental or the second-harmonic modes for plasma heating application [29]- [34]. Kao et al [20], [21] reported that the prior-excited second-harmonic mode increased the threshold current of the competing fundamental mode.…”
Section: Introductionmentioning
confidence: 99%